Real time query propagation strategies with Lightweight Coordination Calculus (LCC) for ad hoc networks of geospatial databases - Bakillah, Mohamed; Zipf, Alexander (Journal of network and computer applications, 2012)
Large volumes of geospatial data are increasingly made available through dynamic networks, such as ad hoc networks. Consequently, new adapted query propagation approaches that take into account geospatial aspects of data are needed. Different existing query propagation approaches use various criteria to select relevant sources. In addition, many approaches rely on existing semantic mappings between sources; however, in ad hoc networks, sources move autonomously and in a dynamic fashion. Our goal is rather to reduce the number of sources that must be accessed to answer a query and, therefore, to reduce the volume of semantic mappings that needs to be computed to answer the query. In this paper, we propose three real time query propagation strategies to address this issue. Those strategies reproduce the behavior of members of a social network. The strategies are designed to be part of a real time semantic interoperability framework for ad hoc networks of geospatial databases. The strategies have been formalized with the Lightweight Coordination Calculus (LCC), which support distributed interactions based on social norms and constraints. The implementation and testing of the strategies show that they complement each other to provide optimal query answers.